Thermomineral waters of inner Dinarides Karst - Dejan Milenić; Olivera Krunić; Djuro Milanković (Acta Carsologica, 2012)
The Dinarides are the largest continuous karst region in Europe. With regard to a geotectonic view, they are divided into the Outer, Central and Inner Dinarides occupying the territories of Slovenia, Croatia, Bosnia and Herzegovina, Serbia and Montenegro. Numerous occurrences of thermomineral water have been recorded in the Inner Dinarides area. The majority of them are genetically related to carbonate sediments of Mesozoic age. This paper deals with occurrences of thermomineral waters of the Inner Dinarides karst, their quantitative and qualitative characteristics, basic genetic types, the age of karst thermomineral waters of the Inner Dinarides, the available quantities of hydrogeothermalmineral energy, balneological potential and the possibility of rational multi-purpose utilisation. Hydrochemical and isotope methods have been used for the analysis of basic genetic types and age of karst thermomineral waters, while a geothermometer method has been used for the calculation of primary temperatures in water-bearing horizons(geothermal reservoirs) themselves. The carried out research has pointed out that karst thermomineral waters formed in carbonate sediments of Mesozoic age are characterized by temperatures ranging from 15.5oC (Knežina Ilidža) to 75oC (Bogatić), being most frequently of a HCO3-Ca, Mg type with neutral to poor alkaline reaction and mineralization below 1 g/l. Karst thermomineral waters of the Inner Dinarides are most frequently related to geothermal systems formed in carbonate sediments covered by rocks of poor water permeability. In case of some thermomineral water occurrences, the mixing of the karst thermomineral waters with those formed in sedimentary basins occurs due to their hydraulic relation, thus it is not possible to determine only one geothermal system in which they are formed. The overall geothermal potential of the thermomineral waters of the Inner Dinarides karst is about 160 MW. In addition to the geothermal aspect, these waters  have been widely utilised in balneology, wellness programmes, as well as for the needs of bottling. The level of research activity and with that the way of the utilisation of these waters are various. With regard to the number of occurrences known so far and their potential, it can be claimed with certainty, that the utilisation of thermomineral water occurring in the karst of the Inner Dinarides will increase significantly in future. An example of the multi-purpose utilisation of the Pribojska Banja Spa thermomineral waters illustrates a possible way of doing it.